2023
DOI: 10.3390/pharmaceutics16010015
|View full text |Cite
|
Sign up to set email alerts
|

Topical Insulin in Neurotrophic Keratopathy: A Review of Current Understanding of the Mechanism of Action and Therapeutic Approach

Marcin Jaworski,
Anna Lorenc,
Rafał Leszczyński
et al.

Abstract: Neurotrophic keratopathy is a corneal disease characterized by impaired corneal innervation. It can lead to corneal epithelial defects, ulcerations, and perforations. Topical insulin has been shown to be effective in treating this disorder. Insulin is a growth factor that can promote corneal epithelial cell proliferation and migration. In addition, it can also inhibit corneal epithelial cell apoptosis. Topical insulin has previously been found to enhance corneal wound healing. This article reviews the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…It is worth noting that topical insulin has been explored and has shown promising outcomes in the management of diabetic keratopathy [170]. Mechanistically, insulin has the ability to counteract the downregulation of the PI3K/Akt axis linked to ROS.…”
Section: Counteracting Oxidative Stress and Inflammationmentioning
confidence: 99%
“…It is worth noting that topical insulin has been explored and has shown promising outcomes in the management of diabetic keratopathy [170]. Mechanistically, insulin has the ability to counteract the downregulation of the PI3K/Akt axis linked to ROS.…”
Section: Counteracting Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Interestingly, a recent culture study with ocular surface cells showed that drops from plasma rich in growth factors were superior to topical insulin at two different concentrations (1 and 0.2 IU/m) in promoting wound healing and reducing the fibrosis process [ 115 ]. Currently, no universal protocol exists regarding treatment with topical insulin, as studies apply different preparation methods, dosages, concentrations, and types of drops [ 116 , 117 ].…”
Section: The Role Of Insulin and Effect Of Diabetesmentioning
confidence: 99%
“…The systematic review carried out, covering a thorough search of various databases (PubMed, Scopus, Science Direct, Scielo, Bireme, Google Scholar and Web of Science), provided an indepth analysis of the use of insulin eye drops in the treatment of neurotrophic corneal ulcers. Jaworski et al [3], in their review of the current understanding of the mechanism of action and therapeutic approach, emphasised the importance of understanding corneal insulin receptors, highlighting the need for further studies to fully elucidate this process. It serves as a crucial foundation for understanding the molecular and pharmacological aspects involved in the proposed treatment.…”
Section: State-of-the-art Research Into the Use Of Insulin Eye Drops ...mentioning
confidence: 99%
“…Researchers have contributed significantly to this analysis, offering diverse and enriching perspectives. Such as Jaworski et al [3], who emphasised the importance of assessing the response of corneal insulin receptors. They also highlighted clinical variables related to the expression of these receptors, providing insights into possible correlations with the clinical efficacy of the treatment.…”
Section: Analysis Of Clinical Variables Outcomes and Safety Measures ...mentioning
confidence: 99%
See 1 more Smart Citation